Sustainable tourism in islands and small states : issues and policies (London : Pinter, 1996)
This book is about: Sustainable tourism; Tourism development in small Island States; Island states and the problems of mass tourism; ...
Keywords: Tourism; Congresses; Tourism -- Congresses